The Healthy Toddlers Trial Protocol: An Intervention to Reduce Risk Factors for Childhood Obesity in Economically and Educationally Disadvantaged Populations - Auld Garry; Coleman Gayle; Baker Susan; Horodynski Mildred A; Lindau Joel (BMC, 2011)
Abstract Background The number of overweight children in America has doubled to an estimated 10 million in the past 20 years. Establishing healthy dietary behaviors must begin early in childhood and include parents. The Healthy Toddlers intervention focuses on promoting healthy eating habits in 1- to 3-year-old children utilizing the Social Cognitive Theory and a learner-centered approach using Adult Learning principles. This Healthy Toddlers Trial aims to determine the efficacy of a community-based randomized controlled trial of an in-home intervention with economically and educationally disadvantaged mothers of toddlers. The intervention focuses on: (a) promoting healthy eating behaviors in toddlers while dietary habits are forming; and (b) providing initial evidence for the potential of Healthy Toddlers as a feasible intervention within existing community-based programs. Methods/Design This describes the study protocol for a randomized control trial, a multi-state project in Colorado, Michigan, and Wisconsin with economically and educationally disadvantaged mother-toddler dyads; toddlers are between 12 and 36 months. The Healthy Toddlers intervention consists of eight in-home lessons and four reinforcement telephone contacts, focusing on fruit, vegetable, and sweetened beverage consumption and parental behaviors, taught by paraprofessional instructors. Healthy Toddlers uses a randomized, experimental, short-term longitudinal design with intervention and control groups. In-home data collection (anthropometric measurements, feeding observations, questionnaires, 3-day dietary records) occurs at baseline, immediately following the intervention, and 6 months after the intervention. Main toddler outcomes include: a) increased fruit and vegetable consumption and decreased sweetened beverage consumption; and b) improved toddler-eating skills (self-feeding and self-serving). Main parent outcomes include: a) improved psychosocial attributes (knowledge, attitudes, self-efficacy, feeding style) related to child feeding; b) provision of a more positive mealtime physical environment (turning off the TV); and c) creation of a more positive mealtime social environment (sitting down together for meals). Discussion If this project is successful, the expected outcomes are that the intervention will be effective in helping toddlers develop healthy eating skills that contribute to improve overall health and development and to the prevention of obesity. Trial registration Current Controlled Trials ACTRN12610000981022